2014
DOI: 10.1177/1420326x14534865
|View full text |Cite
|
Sign up to set email alerts
|

Integrated exposure for risk assessment in indoor environments based on a review of concentration data on airborne chemical pollutants in domestic environments in Europe

Abstract: This review set out to identify data sets for airborne chemical pollutants measured in domestic dwellings within European Union (EU) countries from the literature published during 1995–2010. A total of 74 papers satisfied inclusion criteria, and from those papers data on country location, population sampled, sampling period, number of samples and summary statistics of concentrations measured were gathered. The chemical substances identified and included were grouped to aldehydes, radon, carbon dioxide (CO2), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 86 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…By exploring the studies and scientific papers of past twenty years in online databases, it was revealed that a number of prominent nation and global-wide projects regarding the IAQ were conducted [84,85]. These projects aimed the investigation of IAQ in various indoor environments in different themes of health, energy, socio-economy and risk management.…”
Section: Iaq Target-oriented Projectsmentioning
confidence: 99%
“…By exploring the studies and scientific papers of past twenty years in online databases, it was revealed that a number of prominent nation and global-wide projects regarding the IAQ were conducted [84,85]. These projects aimed the investigation of IAQ in various indoor environments in different themes of health, energy, socio-economy and risk management.…”
Section: Iaq Target-oriented Projectsmentioning
confidence: 99%
“…The most abundant formaldehyde, together with acetaldehyde and hexanal, are detected in 100% of French dwellings . Due to their possible impact on human health the monitoring of these compounds in indoor air is of major interest . The main indoor sources of aldehydes are building materials, paints and furniture, as shown by the numerous papers dealing with the emissions of aldehydes in air by materials .…”
Section: Introductionmentioning
confidence: 99%
“…2 Due to their possible impact on human health the monitoring of these compounds in indoor air is of major interest. 3,4 The main indoor sources of aldehydes are building materials, paints and furniture, as shown by the numerous papers dealing with the emissions of aldehydes in air by materials. 1,[5][6][7] Outdoors, aldehydes are released into the atmosphere by vehicle exhaust and incomplete combustion of hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution could have many adverse effects on human health. The behaviour of indoor air pollutants emissions is of great importance to regulate air quality and assess health risks, such as fine and ultrafine particular matters (PM 10 and PM 2.5 ), 9 formaldehyde, 10,11 VOCs, 12 airborne fungi, 13 nitrogen oxides (NO x ), 14 ozone (O 3 ) 15 and radon. 16,17 Also carbon dioxide (CO 2 ) 18,19 concentration should be included for consideration as this has a significant relationship with ventilation efficiency, occupants’ respiratory index related to tiredness and sick building syndrome symptoms.…”
mentioning
confidence: 99%